Correlates of Facebook use Intensity - A Saudi Arabian Study - Alayaf, Abeer (Université d'Ottawa / University of Ottawa, 2015)
This study measures Facebook use intensity in residents of Saudi Arabia, and distinguishes between Saudi citizens and non-Saudi residents. This is achieved through an analysis of the antecedents and the consequences of Facebook use intensity. The sample used consists of 135 Saudi and 66 non-Saudi participants, all of whom were Facebook users aged 18 or older. The “snowball” technique was used in this study. Data was collected through a face-to-face questionnaire, and analyzed using IBM SPSS Statistics. Results show that there were significant relationships between the antecedents and the consequences of Facebook use intensity. Non-Saudi residents are shown to use Facebook to keep in touch with their families and friends more than Saudi do, while Saudi citizens use Facebook to search for products more than non-Saudi. The two groups are also quite different in terms of their online shopping behavior, including the sources of information and recommendations they prefer when researching a product. This study shows that there is a relationship between participants’ Facebook usage, and their demographics, personality, motivations, and values. The major limitation of this study is that it was conducted in only one city: Riyadh. Therefore, additional research should be carried out in other cities with larger samples. This thesis makes a special contribution to the literature, as it is the first to consider both the antecedents and the consequences of Facebook use intensity in a single study. It is also the first study to analyze the relationship between the Six Dimensional Achievement Motivation Scale (Jackson, Ahmed, and Heapy, 1976), the Rokeach Value System (1973), and Facebook use intensity in the world in general, and Saudi Arabia in particular.
Keywords: Facebook Intensity; Social media